2020
DOI: 10.1073/pnas.2009799117
|View full text |Cite
|
Sign up to set email alerts
|

Syrian hamsters as a small animal model for SARS-CoV-2 infection and countermeasure development

Abstract: At the end of 2019, a novel coronavirus (severe acute respiratory syndrome coronavirus 2; SARS-CoV-2) was detected in Wuhan, China, that spread rapidly around the world, with severe consequences for human health and the global economy. Here, we assessed the replicative ability and pathogenesis of SARS-CoV-2 isolates in Syrian hamsters. SARS-CoV-2 isolates replicated efficiently in the lungs of hamsters, causing severe pathological lung lesions following intranasal infection. In addition, microcomputed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

161
1,241
7
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,029 publications
(1,424 citation statements)
references
References 31 publications
161
1,241
7
15
Order By: Relevance
“…To date, the Syrian golden hamster is the only animal species in which experimental SARS-CoV-2 infection results in moderate to severe pneumonia, with clinical signs, as well as shedding of virus 12,13,15 . Therefore, the prophylactic potential of the 47D11 MAb and convalescent human plasma was evaluated in this hamster model.…”
Section: Neutralizing Antibodies Protect Against Body Weight Loss Fromentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the Syrian golden hamster is the only animal species in which experimental SARS-CoV-2 infection results in moderate to severe pneumonia, with clinical signs, as well as shedding of virus 12,13,15 . Therefore, the prophylactic potential of the 47D11 MAb and convalescent human plasma was evaluated in this hamster model.…”
Section: Neutralizing Antibodies Protect Against Body Weight Loss Fromentioning
confidence: 99%
“…Results from a randomized clinical trial did not show a benefit 6,7 , while results from the small cohorts suggested clinical benefit but lacked controls for proper interpretation [8][9][10][11] . Although preclinical research indicated a limited protective effect of hamster serum when given to hamsters infected with SARS-CoV-2 early in the disease course 12,13 , effects of human plasma have not been analyzed in this animal model. Importantly, data on the level of neutralizing antibodies that are required to provide a clinically meaningful protective effect are not available.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction analysis of mutated and wild type RBDs with ACE2 receptor indicated that bats and pangolins could be suitable natural reservoirs for Indian isolates of this virus and this finding falls parallel with other earlier reports 29,30 . As hamster has been reported as a suitable animal model to study SARS-CoV-2 pathogenesis, the interaction of RBD of the Indian isolates included in the current study makes the earlier report more relevant 10 . Though the susceptibility of infection and death rate could be affected by several factors, mutation in the virus genome and its ability to adapt to new environment could be crucial.…”
Section: Discussionmentioning
confidence: 89%
“…From the phylogenetic tree analysis, four RMRC RBD sequences were selected from four random clusters for further investigation of their interactions with ACE2 receptor of probable natural hosts of SARS-CoV-2. Hamsters were reported to be the best suitable animal model to carry out SARS-CoV-2 related experiments; therefore it was essential to understand the interaction of its ACE2 receptor with isolated Indian SARS-CoV-2 RBDs 10 Chinese and Indian bat, which has prompted us to predict their three dimensional (3D) structure through homology modelling using Modeller v 9.19 tool followed by structure validation. Suitable templates were identified for 3D model building of ACE2 using BLASTp 11 search against PDB (Protein Data Bank) database.…”
Section: Sequence and 3d Structure Analysis Of Ace2 Receptormentioning
confidence: 99%
“…Several steps in viral replication could be affected including entry/fusion, lipid metabolism related to budding, formation of replication complexes, secretory pathway function and affects on SARS-CoV-2 protein processing, etc. Also, in vivo studies with animal models such as transgenic mice (27), hamsters (28), ferrets (29) or nonhuman primates (30) should be conducted, and oleandrin should be tested for antiviral activity against SARS-CoV and MERS-CoV.…”
Section: Discussionmentioning
confidence: 99%